2020
DOI: 10.3928/1081597x-20200303-01
|View full text |Cite
|
Sign up to set email alerts
|

Interaction of Monochromatic and Chromatic Aberrations in Pseudophakic Patients

Abstract: PURPOSE: To measure monochromatic aberrations at various wavelengths in eyes implanted with the Clareon monofocal aspheric intraocular lens (IOL) (Alcon Laboratories, Inc., Fort Worth, TX). The authors estimated longitudinal chromatic aberration (LCA), modulation transfer functions (MTFs), and the impact of interactions between chromatic and monochromatic aberrations on retinal image quality. METHODS: Ten patients (age: 68.4 ± 3.21 years) were measured … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 28 publications
1
5
0
Order By: Relevance
“…patient (19). Regarding chromatic aberration, Marcos et al,(20) recently assessed LCA with a psychophysical test in a group of 10 patients implanted with the Clareon® IOL model; they reported a mean LCA value of 1.23 ± 0.05 D. These values are totally in line with those from our study (1.23 ± 0.49 D, Table…”
supporting
confidence: 91%
“…patient (19). Regarding chromatic aberration, Marcos et al,(20) recently assessed LCA with a psychophysical test in a group of 10 patients implanted with the Clareon® IOL model; they reported a mean LCA value of 1.23 ± 0.05 D. These values are totally in line with those from our study (1.23 ± 0.49 D, Table…”
supporting
confidence: 91%
“…This is consistent with a previous study where patients were bilaterally implanted with monofocal IOLs of the same design, but with hydrophobic material in one eye and hydrophilic material in the contralateral eye. 13 In that study, there was a constant offset of 0.15 D between the LCA measured in vivo in eyes implanted with monofocal IOLs of both materials, which compares with the offset in the LCA found between the hydrophobic and hydrophilic trifocal IOL at far (0.17 D). However, the magnitude of the LCA in patients implanted with monofocal IOL designs was higher (1.37 ± 0.08 D for the hydrophobic and 1.2.1 ± 0.08 D for the hydrophilic) than with the corresponding trifocal designs.…”
Section: Discussionmentioning
confidence: 76%
“…Various studies report the LCA of lenses with different materials, both on bench and once implanted in the eye. [6][7][8][9][10][11][12][13] For example, the psy-chophysical LCA (480 to 700 nm) in phakic eyes has been reported to be 1.52 diopters (D), 5 whereas LCA was 1.37 ± 0.08 D in patients implanted with hydrophobic monofocal IOLs (FineVision hydrophobic raw material) and 1.21 ± 0.08 D in patients implanted with hydrophilic monofocal IOLs (FineVision hydrophilic raw material). 14 Besides the material, the design of the IOL 15 also influences the chromatic aberrations of IOLs.…”
mentioning
confidence: 99%
“…Although VA exhibits a robust response under modified chromatic conditions, the authors reported impairment in the predictability of the results with an LCA modified from natural conditions, as the experimental VA values were lower than the predicted. Marcos et al 45 reported in a recent paper that psychophysical LCA was consistently larger than objective LCA in a group of patients implanted with a monofocal IOL. Such reports indicate that clinical applications of in vitro measurements and simulations using eye models are of great interest, and studies are currently proceeding at a rapid pace, although much additional research is required.…”
Section: Discussionmentioning
confidence: 94%